ANALYSIS OF SEBT TEST INDICATORS OF MALE REPRESENTATIVES OF KYOKUSHINKAI KARATE AND BOXING IN A SIX-MONTH MEASUREMENT INTERVAL - Kindzer, B. M.; Nikitenko, S. A.; Skalski, D. W. (Rehabilitation and Recreation, 2024)
Purpose – to compare SEBT indicators, obtained with a six-month interval of measurements in male representatives from Kyokushinkai karate and boxing. Materials and methods. The results of the study were obtained at the Ivan Bobersky Lviv State University of Physical Culture in May and November 2023. Physically healthy, uninjured male qualified boxers (n=8) and Kyokushinkai karate athletes (n=10) aged 18–22 years, who are University students, took part in the collection of experimental material. Research methods: the analysis of literary sources and Internet; measurement of Star Excursion Balance Test indicators; methods of mathematical statistics. Research results. The results confirmed the overall reproducibility of the SEBT test. Differences in SEBT positions in both types of martial arts were unreliable in the absolute majority of indicators, except for position 7 among boxers and position 6 among representatives of Kyokushinkai karate. The indicated individual positions had a significantly better result after six months of training athletes in both types of martial arts after the first measurement. SEBT indicators demonstrate the asymmetric influence of the left-sided combat stance on the motor balance for all boxers, regardless of their training scheme or training program: left leg tend to deteriorate in positions 2, 3, 4, 5, 6, 7, and 8 (position 1 remained unchanged); right pushing leg improved in positions 4, 6, and 7, and slightly decreased in positions 1, 2, 3, and 5 (position 8 remained unchanged); left arm experienced an improvement trend in almost all positions (from 2 to 8); right arm show trends for improvement in positions 2, 3, 4, and 5, and some deterioration in positions 1, 6, 7 and 8. Kyokushinkai karate athletes showed: a trend toward improvement in most of the left leg SEBT measures; most of the SEBT positions of the left arm tend to deteriorate; SEBT indicators of the right leg improved in the “lower” positions 3, 4, and 5, but positions 6 and 8 are slightly worsened; most of the right arm positions during the half-year training period tend to deteriorate. Conclusion. The SEBT technique has high reliability and reproducibility of results over time. The results of SEBT in long time intervals (half a year, for example) can reflect the influence of a certain sport on the amplitude of movements and dynamic balance of athletes.